Pangenomic analysis of Wolbachia provides insight into the evolution of host adaptation and cytoplasmic incompatibility factor genes - Liu, Bo; Ren, Ye-Song; Su, Cheng-Yuan; Abe, Yoshihisa; Zhu, Dao-Hong (Frontiers in Microbiology, 2023)
Introduction The genus Wolbachia provides a typical example of intracellular bacteria that infect the germline of arthropods and filarial nematodes worldwide. Their importance as biological regulators of invertebrates, so it is particularly important to study the evolution, divergence and host adaptation of these bacteria at the genome-wide level. Methods Here, we used publicly available Wolbachia genomes to reconstruct their evolutionary history and explore their adaptation under host selection. Results Our findings indicate that segmental and single-gene duplications, such as DNA methylase, bZIP transcription factor, heat shock protein 90, in single monophyletic Wolbachia lineages (including supergroups A and B) may be responsible for improving the ability to adapt to a broad host range in arthropod-infecting strains. In contrast to A strains, high genetic diversity and rapidly evolving gene families occur in B strains, which may promote the ability of supergroup B strains to adapt to new hosts and their large-scale spreading. In addition, we hypothesize that there might have been two independent horizontal transfer events of cif genes in two sublineages of supergroup A strains. Interestingly, during the independent evolution of supergroup A and B strains, the rapid evolution of cif genes in supergroup B strains resulted in the loss of their functional domain, reflected in a possible decrease in the proportion of induced cytoplasmic incompatibility (CI) strains. Discussion This present study highlights for reconstructing of evolutionary history, addressing host adaptation-related evolution and exploring the origin and divergence of CI genes in each Wolbachia supergroup. Our results thus not only provide a basis for further exploring the evolutionary history of Wolbachia adaptation under host selection but also reveal a new research direction for studying the molecular regulation of Wolbachia- induced cytoplasmic incompatibility.